Peptone from casein: its influence in the transcription of lanthipeptides and the proteome of Pedobacter lusitanus NL19 - Gomes, Margarida de Sousa (2023)
Pedobacter lusitanus NL19 is a Gram -negative bacterium from the famil y Sphingobacteriaceae, which was isolated from a deactivated uranium mine in Portugal. This strain produces non ribosomal peptides (NRPs), calle d pedopeptins. The production of these peptides is repressed by high concentrations of peptone from casein (PC). In addition to biosynthetic gene clusters (BGCs) encoding NRPs, the NL19 strain genome also has BGCs of other secondary metabolites (SMs), incl uding lanthipeptides (4 BGCs: ped8, ped 14, ped15 and ped17). Lanthipeptides are ribosomally synthesized and post -translationally modified peptides (RiPPs), which exhibit a wide variety of biological activities, including antimicrobial and antiallodyni c. Lanthipeptides are characterized by the presence of lanthionine (Lan) and meth yllanthionine (MeLan) residues and are divided into four classes, defined by the enzymes that catalyze the reactions needed for the installation of these residues. T his s tudy focused on the NL19 strain and the main objectives were to determine the effect of high concentrations of PC: i) on the transcription of lanthipeptides and ii) on the proteome of the strain, with special interest in proteins involved in the biosy nthesis of SMs. Due to the COVID -19 pandemics and confinement, a third objective was defined , w hich aimed to identify and analy z e, in silico, lanthipeptide BGCs from the genomes of other genera of th e family Sphingobacteriaceae. Objective i) involved the transcriptional analysis of BGC ped 1 5 that encodes two precursor peptides and other biosynthetic proteins. It was necessary to s e quence the upstream region of this cluster, through primer walking, whi ch allowed the identification of six other structural peptide genes. The transcriptional analysis was performed by RT -qPCR and revealed that high concen trations of PC do not affect the expression of the BGC ped15, contrary to what was found fo r the pedope ptin s BGC . In general, the RT -qPCR results validated the available RNA -seq results and showed that the transcriptional repression caused by high concentrations of P C is not transversal to t he production of other SMs. Objective ii) involved t he analysis of the proteome of the NL19 strain grow n in high concentrations of PC (and its control) by nano LC -ESI -MS/MS and allowed the detection of the differential expression of some proteins relat ed to the biosynthesis of SMs, including the pedopeptins nonribo somal peptide synth etases and a lanthipeptide precursor encoded in the ped8 BGC. Objective iii) involved the analysis of 446 BGCs of the family Sphingobacteriaceae with the antiSMASH and Bi G -SCAPE tools. Class I and class III lanthipeptide BGCs were ide ntified in the gene ra Mucilaginibacter and Sphingobacterium. Class III BGCs encode La nKC enzymes with slightly different lyase domains, which may indicate that these enzymes use a different me chanism for the installation of Lan /MeLan. This stu dy contributes to the bo dy of knowledge of the bacterial response to the manipulation of culture media, in particular in the production of SMs with biotechnological potential as lanthipeptide s. In addition, this study identified the potential of bacterial genera already known, but still unde rex plored, for the production of new lanthipeptides, whose biosynthetic, structural and functional characterization is unknown.